Analysis of Bottom Gillnet Catches in Lambur Luar Village, Muara Sabak Timur District, Tanjung Jabung Timur Regency - Khairunissa, Ade; Mairizal; Magwa, Rizky Janatul; Lisna; Ramadan, Fauzan; Wulandari (Journal of Fish Health, 2025)
The waters of Lambur Luar Village are a productive coastal area that supports capture fisheries activities, one of which is through the use of bottom gillnets. This fishing gear is considered fairly selective and environmentally friendly, making it important to assess its effectiveness in terms of catch composition. This study aims to analyze the main catch, bycatch, and discard from bottom gillnets operated by local fishers. The method used was a survey with purposive sampling on ten fishing units, with four replications per unit. The data were analyzed descriptively and supported by biodiversity indices, including diversity, evenness, and dominance. The results showed that mantis shrimp (Harpiosquilla raphidea) was the dominant main catch, with the highest number and biomass. Bycatch was dominated by demersal fish such as croaker (Johnius trachycephalus), tongue sole (Cynoglossus lingua), Chacunda gizzard shad (Anodontostoma chacunda), fourfinger threadfin (Eleutheronema tetradactylum), along with several other species. Meanwhile, discards consist of non-economic benthic organisms such as snails, starfish (Asteroidea spp.), horseshoe crabs (Tachypleus gigas), and ghost crabs (Ocypoda quadrata). The diversity index indicated a moderate category, reflecting ecosystem balance, while the dominance index was low, suggesting no single species excessively dominated the ecosystem. In conclusion, bottom gillnets with a mesh size of 3.5 inches proved effective in capturing target organisms suitable for consumption while reducing the proportion of unwanted discards. This indicates that bottom gillnets have the potential to support sustainable fisheries practices without causing significant negative impacts on the benthic ecosystem in the waters of Lambur Luar Village.